2008
DOI: 10.1055/s-0037-1617374
|View full text |Cite
|
Sign up to set email alerts
|

Review and retrospective analysis of degenerative lumbosacral stenosis in 156 dogs treated by dorsal laminectomy

Abstract: The medical records of 156 dogs with degenerative lumbosacral stenosis (DLS) that underwent decompressive surgery were reviewed for signalment, history, clinical signs, imaging and surgical findings. The German Shepherd Dog (GSD) was most commonly affected (40/156, 25.6%). Pelvic limb lameness, caudal lumbar pain and pain evoked by lumbosacral pressure were the most frequent clinical findings. Radiography showed lumbosacral step formation in 78.8% (93/118) of the dogs which was associated with elongation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
89
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 33 publications
(62 reference statements)
12
89
0
4
Order By: Relevance
“…Degenerative lumbosacral stenosis (DLSS) is a common condition of middle-aged and older large breed dogs, particularly German Shepherd and working dogs, leading to potentially debilitating pain and neurological deficits (Oliver et al 1978;Danielsson and Sjöstrom 1999;Suwankong et al 2008). Neurological dysfunction is related to compression of the cauda equina nerve roots secondary to pathophysiologic processes such as intervertebral disk protrusion, articular facet joint misalignment, and chronic lumbosacral instability (Lenehan and Tarvin 1998;De Risio et al 2001;Benninger et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative lumbosacral stenosis (DLSS) is a common condition of middle-aged and older large breed dogs, particularly German Shepherd and working dogs, leading to potentially debilitating pain and neurological deficits (Oliver et al 1978;Danielsson and Sjöstrom 1999;Suwankong et al 2008). Neurological dysfunction is related to compression of the cauda equina nerve roots secondary to pathophysiologic processes such as intervertebral disk protrusion, articular facet joint misalignment, and chronic lumbosacral instability (Lenehan and Tarvin 1998;De Risio et al 2001;Benninger et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Se halló una alta frecuencia de presentación de ILS en canes Labrador Retriever (75%, 45/60) mediante la evaluación radiológica, frecuencia bastante similar a los datos obtenidos por Ness (1994) y Suwankong et al (2008), quienes reportan frecuencias de 70.0 y 78.8%, respectivamente, en estudios con varias razas, incluyendo el Labrador Retriever.…”
Section: Discussionunclassified
“…Uno de los segmentos afectados es el segmento lumbosacro, donde se encuentra la cauda equina, conjunto de nervios periféricos que abandonan caudalmente la médula espinal (Suwankong et al, 2008).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Osteophyte formations extending dorso-laterally can compress spinal nerve roots at the level of intervertebral foraminae (Morgan et al 1989). Spondylosis was also detected on computed tomography (CT) images in 62% of dogs with degenerative lumbosacral stenosis (DLS) (Suwankong et al 2008). Although the presence of spondylosis has been suggested to be correlated with Hansen's type 2 disc protrusion (Levine et al 2006), spondylosis is also found in combination with healthy intervertebral discs.…”
Section: Clinical Signsmentioning
confidence: 97%